Consequences of the Soviet Ethnic Federalism in the South Caucasus - Elaheh Koolaee (Banber Arevelagitut'yan Instituti)
The roots of Islam in the beliefs and thoughts of the people of the Caucasus region go back to the seventh century and it has grown during many years in the course of various developments. The creation of the “Green Belt” by the USA during the Cold War also promoted Islamic tendencies in the peripheral regions of the Soviet Union. After the military attack of the Red Army on Afghanistan, Islamist movements had a better opportunity to enjoy the support of the United States of America against the Soviet Union. The resurgence of Islamic trends in the Middle East and West Asia affected the Caucasus region as well. The conditions created by the implementation of Gorbachev's reform policies were also very suitable for Islamism. While the ethnic policies of the Soviet Union and the “ethnic federalism” of the communist system were entering a new stage, Islamism was also strengthened by using the space created by the implementation of Glasnost. The effects of ethnic-racial policies of the Soviet Union on the political- military trends in the Caucasus, after the collapse, is the aim of this review.